Land redistribution and state decentralisation in South Africa - Jaricha, Desmond Tichaona (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
South Africa is a new democracy that has had to deal with many historical remnants of apartheid. One of the main remnants has been land dispossession and massive inequalities along racial lines of access to land for agricultural purposes. In countering this, the post-apartheid state has pursued land redistribution programmes since the end of apartheid in 1994, as part of a broader land reform project. Simultaneously, post-apartheid South Africa has been marked by significant state restructuring notably a process of state de-centralisation including the positioning of municipalities as development agents. Amongst other goals, this is designed to democratise the state given the authoritarian and exclusive character of the apartheid state, and thereby to democratise development initiatives and programmes. Land redistribution and state decentralisation in South Africa are different political processes with their own specific dynamics. They have though become interlinked and intertwined but not necessarily in a coherent and integrated manner. Within broader global developments pertaining to state decentralisation and land redistribution, the thesis examines the complex relations between these two processes in South Africa. In particular, I analyse critically the decentralised character of the land redistribution programme in South Africa. In order to concretise and illustrate key themes and points, I discuss a particular land redistribution project called Masizakhe located in Makana Municipality in the Eastern Cape Province.
Keywords: Land reform -- South Africa; Land tenure -- South Africa; Agriculture -- Economic aspects -- South Africa; Decentralization in government -- South Africa; Local government -- South Africa; South Africa -- Politics and government